STRATEGY OF EDUCATORS IN INSTILLING THE MORAL VALUES OF STUDENTS IN BABUSSALAM JUNIOR HIGH SCHOOL, SELAYAR ISLANDS REGENCY (International Conference on Social and Islamic Studies, 2022)
This study discusses the strategy of educators in instilling the moral values of students in Babussalam Junior High School, Selayar Islands Regency. The objectives of this research are; 1) To find out the form of implementing moral values in the religious life of students at Babussalam Junior High School, Selayar Islands Regency. 2) To find out the obstacles faced by educators in instilling the moral values of students in Babussalam Junior High School, Selayar Islands Regency. 3) To find out the results of the educator's strategy in inculcating moral values in the religious life of students at Babussalam Junior High School, Selayar Islands Regency. This type of research is qualitative, namely examining objects that describe facts in the field as they are, or revealing phenomena in the field contextually with the data collection procedures obtained. The results of this study indicate that: The strategy for inculcating moral values ​​in the religious life of students at Babussalam Junior High School, Selayar Islands Regency, namely, firstly inculcating moral values ​​to students at Babussalam Selayar Junior High School, namely, the existence of disciplinary rules set at Babussalam Selayar Junior High School, there is learning about morals in the classroom, educators make themselves as role models or examples, there is learning outside formal learning. The two strategies of educators in instilling moral values ​​in students at Babussalam Selayar Middle School are supervision, the application of rules or sanctions, setting a good example, and getting students to pray in congregation in the mosque. The three obstacles faced by educators in instilling moral values ​​to students at Babussalam Selayar Junior High School are the regulations in giving sanctions that are not too excessive, the student association factor, the parent factor, and the lack of student discipline. The implications of the research are for educators to pay more attention and always supervise students, so that students obey the rules applied at school and there are still many parents who protest against the sanctions imposed by the school, so the researchers offer socialization to provide an awareness process to parents regarding with the sanctions imposed by the school